Revoicing Attitude of Virginity Test: An Appraisal-based Translation Study on News Discourse - Kholifah, Asrofin Nur; Setiawan Prasetyoningsih, Tri Wahyu (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
The virginity test is a long-standing tradition that has been documented in at least 20 countries around the globe (WHO, 2018). Women and girls are frequently subjected to or forced to undergo this test for various reasons. In the Indonesian context, this gynecological examination conducted under the belief to determine if a woman has had vaginal intercourse has to be experienced by female military candidates. In response, the Indonesian army has set to remove this somewhat controversial policy. Through media, this issue was packed in such a way that reflects the media's stance. Accordingly, this research aims to investigate how media take a stance toward this issue and how the translated version delivers it from the perspective of translation studies and appraisal theory using the qualitative method. Appraisal resources identified the data and compared the original text to the Indonesian versions retrieved from the ABC online news portal (Australian and Indonesia-based). This method is conducted to gather and interpret any attitudinal resources in both original and translated texts. It reveals that the translated version, compared to the more neutral-sounded original one, exploits a more clear-cut attitude towards the issue. Various attitudinal lexis including invasive, gender-based, victim and abusive, are chosen to revoice her stance that this practice is groundless. Through its translation, the author articulates her attitude louder. It proves that different target readers influence how the information is packed and constructed. As a re-situated text, translation barely occurs in an empty space.